Tuesday

September 30, 2014

September 30, 2014

Posted by **Audrey** on Thursday, May 9, 2013 at 5:18pm.

log[1/6](x^2+x)-log[1/6](x^2-x)=-2

- log[1/6](x^2+x)-log[1/6](x^2-x)=-2 -
**Steve**, Thursday, May 9, 2013 at 5:35pmraise 1/6 to the power

(x^2+x)/(x^2-x) = (1/6)^-2 = 36

(x+1)/(x-1) = 36

x = 37/35

**Answer this Question**

**Related Questions**

math - Logarithm!!! Select all of the following that are true statements: (a) ...

Math Help Please - Which of the following expressions is equal to log (x sqrt-y...

Mathematics - Prove that log a, log ar, log ar^2 is an a.p. Is the following ...

Advanced Functions/ Precalculus Log - 1. Evaluate 4^(log base4 64) + 10^(log100...

Algebra 2 - how do not understand how to do this Log X + Lob (X-3) = 1 I know I ...

math - solve for x without using a calculator 5^(x+1) = 25 i know that x would ...

math(Please help) - 1) use the properties of logarithms to simplify the ...

math - write as a single logarithm: -2logbase3(1/x)+(1/3)logbase3(square root of...

Trigonometry - This is a logs question If u=x/y^2, which expression is ...

TRig WIth LoGs help1!! - i have problem i can't solve and the book is no help.. ...